Thermodynamic analysis of heat exchanging appliances - Shutyuk, Vitaliy; Samiilenko, Serhii; Vasylenko, Sergei (My University, 2013)
The article examines the methodology of thermodynamic analysis and the optimization of heaters and heat exchangers of heat engineering complex of saccharine industry. The authors suggest noncyclic approach to the analysis of efficiency of heat exchanging apparatus, the basis of which is irrefutable fact that irreversibility as physical reason of inefficiency of technical heat engineering systems really exists. Thermodynamic analysis, which was mentioned in the article, assumes determination of measure of irreversibility of processes in the apparatus and energetic efficiency of apparatus in the whole with the help of exceptionally entropy. The measures taken to improve energetic efficiency of apparatus of saccharine factory on the example of the first group of juice heating in front of evaporator system using the given methodology, were fully analyzed. В статті розглянуто методику термодинамічного аналізу та оптимізації підігрівників і теплообмінників теплотехнологічного комплексу цукрового виробництва. Авторами запропоновано нециклічний підхід аналізу ефективності теплообмінних апаратів, в основі якого – беззаперечний факт існування необоротності як фізичного джерела неефективності технічних теплотехнічних систем. Наведений в статті термодинамічний аналіз передбачає визначення міри необоротності процесів в апараті та енергетичної ефективності апарата в цілому, використовуючи виключно ентропію. Застосовуючи дану методику, комплексно проаналізовано заходи з підвищення енергетичної ефективності теплообмінних апаратів цукрового заводу на прикладі першої групи нагрівання соку перед випарною установкою.
Keywords: thermodynamics; heat exchange; process; entropy; exergy of warmth; термодинаміка; теплообмін; процес; ентропія; ексергія; термодинамика; теплообмен; процесс; энтропия; эксергия; кафедра теплоенергетики та холодильної техніки; кафедра технології консервування